2016
DOI: 10.1177/1091581815624397
|View full text |Cite
|
Sign up to set email alerts
|

2-Deoxy-d-Glucose (2-DG)–Induced Cardiac Toxicity in Rat

Abstract: 2- Deoxy–D-Glucose (2-DG) is being developed as a potential anticonvulsant and disease-modifying agent for epilepsy patients; however, during preclinical development, cardiac toxicity has been encountered in rats. This study was performed to determine whether cardiac troponin (cTnI and cTnT), Atrial Natriuretic Peptide (ANP), Brain Natriuretic Peptide (BNP), N-terminal pro-brain natriuretic peptide (NT-proBNP) and/or creatine kinase (CK) could be useful as indicators of 2-deoxy-D-glucose (2-DG) cardiac toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In our studies, we did not find evidence of chronic changes in animal health, systemic metabolism, or body temperature (Supplemental Figure 4) over the course of 2-DG treatment. This is important, as long-term exposure to 2-DG (>2 weeks) has been previously associated with cardiotoxicity (95,96) and hypothermia alone may be neuroprotective after TBI (97-99). 2-DG is already in use clinically to limit tumor growth in cancer patients (based on the Warburg effect, which describes increased glycolytic activity in neoplastic cells), and short-term treatments are well tolerated in humans (75).…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, we did not find evidence of chronic changes in animal health, systemic metabolism, or body temperature (Supplemental Figure 4) over the course of 2-DG treatment. This is important, as long-term exposure to 2-DG (>2 weeks) has been previously associated with cardiotoxicity (95,96) and hypothermia alone may be neuroprotective after TBI (97-99). 2-DG is already in use clinically to limit tumor growth in cancer patients (based on the Warburg effect, which describes increased glycolytic activity in neoplastic cells), and short-term treatments are well tolerated in humans (75).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 2-DG possessed a mannose-like property, which competed with mannose during the initial steps of N-linked glycosylation, resulting in protein misfolding and endoplasmic reticulum stress (Xi et al, 2014). In rat models, 2-DG was encountered as cardiac toxicity, with microscopic findings of vacuolar degeneration and hypertrophy of the endothelial cells of the endocardium (Terse et al, 2016). Studies in tumors have found that at low doses, 2-DG mainly interfered with N-linked glycosylation, resulting in endoplasmic reticulum stress, apoptosis, and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretically optimum 2-DG dose may be at the intersection of the two curves, where~70% slices will stop bursting and remain viable (horizontal dashed line), corresponding to~2.7 mM 2-DG (vertical dashed line). monitored and averted by following brain natriuretic peptide levels (Terse et al 2016). Therefore, 2-DG represents a unique compound with antiseizure and antiepileptic actions.…”
Section: Discussionmentioning
confidence: 99%